Penerapan Teknologi Virtual Reality 360ᴼ Sebagai Media Promosi Gor Alfaka Raya Berbasis Android - Mahyahya Hasfi Syah; Siti Sundari (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
The development of digital technology today opens new opportunities in the field of promotion, one of which is through Virtual Reality (VR) technology. This study aims to implement 360° VR technology as a promotional media for GOR Alfaka Raya based on Android. The method used is the Multimedia Development Life Cycle (MDLC) with six stages: concept, design, material collecting, assembly, testing, and distribution. The result of this research is an Android application that displays interactive 360° VR views of GOR Alfaka Raya areas such as the badminton court, stands, and parking lot. This application allows users to virtually see the GOR facilities without having to visit the location directly, making the promotion more attractive, modern, and effective. It is expected that this application can increase public interest in visiting GOR Alfaka Raya and become an alternative promotional media that is interactive and informative. The results of the study conducted on 20 respondents showed that 52.4% found the application easy to use, 57.1% stated that the 360° view was helpful, and 57.1% felt that the application was fun and interesting to use. Furthermore, 76.2% were interested in using the 360° VR, 52.4% liked the location-switching feature, and 47.6% preferred to visit the sports hall directly. Additionally, 57.1% thought the application was visually appealing, 66.7% said it ran smoothly without lag, and 71.4% agreed that it was suitable for promotional purposes.